Perencanaan Titian Dan Dermaga Sebagai Kebutuhan Infrastruktur Penunjang Parawisata Di Desa Pulau Telo Baru, Kecamatan Selat, Kabupaten Kapuas - Irawan, Andre; Mayer, Stevan Aldo; Ardianto, Dimas; Wardana, Peby; Naji, Milady; Kharisma, Meythio; Kurnia, Yosep; Hamidah, Noor (Fakultas Teknik Universitas Palangka Raya, 2024)
Community Service Program focus on the Independent Campus Learning KKN Program is a community service program initiated by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. This program is expected to train students' creativity, thereby providing the best solutions to problems in society, developing students' abilities in creating new ideas/solutions and providing added value to existing ideas/solutions, and encouraging students to be responsive in solving problems in society. The objectives of community service program activities in 2024 designed a pier as a connecting facility between Pulau Telo Baru Village and the Pulau Telo Baru village tourist island. The main program for designing the pier is the implementation of the Master Plan planned by village officials who want to develop the Telo Baru Village Tourism Island as a tourist island which is expected to become a tourism icon for the Telo Baru Island village. The method uses a combined quantitative method by calculating the structural load of a footbridge and pier using SAP 2000 Analysis software, while the design of the footbridge and pier uses Autodesk Revit software. The results of the community service program activities are planning the structure of the footbridge and pier and designing the footbridge and pier as a tourism facility that can help generate income for the welfare of the village and the village community of Telo Island, Selat District, Kapuas Regency